2015
DOI: 10.1021/sc500783s
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Thermomechanical Properties and Heat Distortion Resistance of Poly(l-lactide) with High Crystallinity under High Cooling Rate

Abstract: In this work, a novel, effective and simple approach to largely improve the thermomechanical properties and heat distortion resistance of biodegradable poly­(l-lactide) (PLLA) by using a new nucleating agent (NA), i.e., itself high-melting-point homocrystallites (hPLLA crystallites) is reported. Specially, hPLLA crystallites with a melting temperature (T m) of 187 °C were introduced into the PLLA matrix with a lower T m, i.e., 168 °C via simply melt blending at 170 °C which is between the T ms of the two PLLAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(45 citation statements)
references
References 42 publications
0
45
0
Order By: Relevance
“…The poor heat resistance, namely low HDT, arises from the low degree of crystallinity during thermal processing, ascribed to the extremely slow crystallization rate of PLLA. Thus, enhancing the degree of crystallinity (X c ) has been considered one of the most convenient approaches to improve the heat resistance of PLLA [35]. Annealing is useful in increasing the X c of PLLA but requires a very long time to finish crystallization and is thus not favorable for practical processing [36].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The poor heat resistance, namely low HDT, arises from the low degree of crystallinity during thermal processing, ascribed to the extremely slow crystallization rate of PLLA. Thus, enhancing the degree of crystallinity (X c ) has been considered one of the most convenient approaches to improve the heat resistance of PLLA [35]. Annealing is useful in increasing the X c of PLLA but requires a very long time to finish crystallization and is thus not favorable for practical processing [36].…”
Section: Introductionmentioning
confidence: 99%
“…Many nucleating agents including carbon fillers, cellulose nanocrystals, talc, crystallites of high-melting-point PLLA (hPLLA), and stereocomplex (SC) crystallites of PLLA and poly(D-lactide) (PDLA) have been employed to enhance the crystallization rate of PLLA [36][37][38][39][40][41][42]. Investigations by Yang et al [35,37] indicated that hPLLA showed the most effective nucleation effect for PLLA when compared to talc and SC crystallites. The melting temperature of hPLLA is very close to that of PLLA; thus, the narrow processing temperature window is unfavorable for practical thermal processing.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[31][32][33][34] Alternatively, the introduction of advanced polymers, featuring higher heat resistance, [35][36][37][38][39] inside the blend, can represent another viable strategy. The use of nucleating agents in the form of mineral fillers can promote the formation of the crystalline phase and at the same time confer additional thermal resistance to the biodegradable polymer.…”
Section: Introductionmentioning
confidence: 99%
“…A high crystalline content can also affect by also promoting the amorphous phase that becomes more rigid in the surrounding of the crystalline phase that results in less sensitive to temperature increase. For this purpose, natural nucleating agents or mineral fillers, which can tune the crystallization behavior of PLA and, in turn, confer additional thermal resistance to the polymer and lower the production costs, are widely investigated in the literature .…”
Section: Introductionmentioning
confidence: 99%